Microglia-independent peripheral neuropathic pain in male and female mice. Issue 11 (4th November 2022) - Tu, YuShan; Muley, Milind M.; Beggs, Simon; Salter, Michael W.
Abstract : Supplemental Digital Content is Available in the Text. It is believed that peripheral neuropathic pain is dependent on activation of microglia in the spinal cord, but human trials targeting these cells have been disappointing. We describe clinically relevant peripheral neuropathic pain hypersensitivity that is microglia-independent in male and female mice. Abstract: The dominant view in the field of pain is that peripheral neuropathic pain is driven by microglia in the somatosensory processing region of the spinal dorsal horn. Here, to the contrary, we discovered a form of neuropathic pain that is independent of microglia. Mice in which the nucleus pulposus (NP) of the intervertebral disc was apposed to the sciatic nerve developed a constellation of neuropathic pain behaviours: hypersensitivity to mechanical, cold, and heat stimuli. However, NP application caused no activation of spinal microglia nor was pain hypersensitivity reversed by microglial inhibition. Rather, NP-induced pain hypersensitivity was dependent on cells within the NP which recruited macrophages to the adjacent nerve. Eliminating macrophages systemically or locally prevented NP-induced pain hypersensitivity. Pain hypersensitivity was also prevented by genetically disrupting the neurotrophin brain-derived neurotrophic factor selectively in macrophages. Moreover, the behavioural phenotypes as well as the molecular mechanisms of NP-induced pain hypersensitivity were not different between males and females. Our findings reveal a previously unappreciated mechanism for by which a discrete peripheral nerve lesion may produce pain hypersensitivity, which may help to explain the limited success of microglial inhibitors on neuropathic pain in human clinical trials.